Low temperature resistivity anomalies in Pr-based nano-manganites - T. Das, Proloy (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The low-temperature electronic transport behavior of under doped polycrystalline Pr0.8Sr0.2MnO3 (PSMO) manganite nanoparticles (down to 40 nm), have been investigated in the presence of applied external magnetic fields (Hext) and a distinct resistivity minimum (Ïmin) is observed below 50 K for each PSMO sample. It has been found that both depth of Ïmin, and temperature of resistivity minima ( ï²min T ) values enhance with increase of Hext. Considering various possibilities like Coulomb blockade theory, electron-electron interaction, phase separation, Kondo mechanism, we conclude that occurrence of low temperature resistivity anomalies (< ï²min T ) in PSMO manganite system is presumably due to a combined effect of electron-electron interaction (~T1/2) and 3D weak localization (WL) mechanism. The proposed model can explain spin dependent scattering phenomena in disorder background of correlated manganite system and behavior of various fit parameters responsible for low temperature resistivity anomalies under external magnetic fields.